Recent Progress in the Development of Fluorescent Probes for the Detection of Hydrazine (N2H4). (2nd January 2022) - Yan, Liqiang; Zhang, Shiqing; Xie, Ya; Mu, Xinyue; Zhu, Jinbiao
ABSTACT: With the widespread use of N2 H4, it brings potential risk to human health and environmental safety because of its diverse toxicological functions. In order to determine N2 H4 effectively in both environment and living systems, all kinds of fluorescence probes have been prepared for the specific response of N2 H4 based on various mechanisms and different acceptor group for N2 H4 . This paper provides a review to bring more inspirations for the development of the fluorescent probes for N2 H4 .